Multiresistant Enterobacteriaceae in yellow‐legged gull chicks in their first weeks of life. Issue 6 (11th June 2022) - Vittecoq, Marion; Brazier, Lionel; Elguero, Eric; Bravo, Ignacio G.; Renaud, Nicolas; Manzano‐Marín, Alejandro; Prugnolle, Franck; Godreuil, Sylvain; Blanchon, Thomas; Roux, François; Durand, Patrick; Renaud, François; et al.
Abstract: Wild animal species living in anthropogenic areas are commonly carriers of antimicrobial‐resistant bacteria (AMRB), but their role in the epidemiology of these bacteria is unclear. Several studies on AMRB in wildlife have been cross‐sectional in design and sampled individual animals at only one point in time. To further understand the role of wildlife in maintaining and potentially transmitting these bacteria to humans and livestock, longitudinal studies are needed in which samples are collected from individual animals over multiple time periods. In Europe, free‐ranging yellow‐legged gulls ( Larus michahellis ) commonly live in industrialized areas, forage in landfills, and have been found to carry AMRB in their feces. Using bacterial metagenomics and antimicrobial resistance characterization, we investigated the spatial and temporal patterns of AMRB in a nesting colony of yellow‐legged gulls from an industrialized area in southern France. We collected 54 cloacal swabs from 31 yellow‐legged gull chicks in 20 nests on three dates in 2016. We found that AMRB in chicks increased over time and was not spatially structured within the gull colony. This study highlights the complex occurrence of AMRB in a free‐ranging wildlife species and contributes to our understanding of the public health risks and implications associated with ARMB‐carrying gulls living in anthropogenic areas. Abstract : We investigated the spatial and temporal patterns of antimicrobial resistant bacteria carriage in a nesting colony of Yellow‐legged Gulls from an industrialized area in Southern France. We found that carriage of antimicrobial resistant bacteria by the chicks increased over time and was not spatially structured within the gull colony. This study highlights the complexity of antimicrobial resistant bacteria carriage in a free‐ranging wildlife species and contributes to our understanding of the public health risks and implications associated with this carriage.